2014
DOI: 10.1002/app.41321
|View full text |Cite
|
Sign up to set email alerts
|

Study on the preparation and thermal shrinkage properties of nano‐SiO2/UHMWPE/HDPE blend microporous membranes

Abstract: Nano-SiO 2 /UHMWPE/HDPE blend microporous membranes (NBMs) with different content of nano-SiO 2 particles were prepared via thermally induced phase separation process. Thermogravimetric analysis was used to investigation of the amount of nano-SiO 2 particles reserved in NBMs. This approach showed that about 59% of total content of nano-SiO 2 particles reserved in NBMs. The formation and development of the interface pores were studied by scanning electron microscopy. NBMs performance was characterized by a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Due to the high viscosity and poor fluidity of UHMWPE, conventional mechanical processing methods are difficult to process, and they are usually formed by special methods, such as thermally induced phase separation (TIPS) [ 26 , 27 , 28 ], thermally induced phase separation stretching (TIPS-S) [ 29 ], melt extrusion stretching [ 30 , 31 ], the nuclear track method [ 32 ], and powder sintering method [ 33 , 34 , 35 ]. Nevertheless, these methods have their deficiencies such as complicated operations, long molding times, and less choice of shape and size of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high viscosity and poor fluidity of UHMWPE, conventional mechanical processing methods are difficult to process, and they are usually formed by special methods, such as thermally induced phase separation (TIPS) [ 26 , 27 , 28 ], thermally induced phase separation stretching (TIPS-S) [ 29 ], melt extrusion stretching [ 30 , 31 ], the nuclear track method [ 32 ], and powder sintering method [ 33 , 34 , 35 ]. Nevertheless, these methods have their deficiencies such as complicated operations, long molding times, and less choice of shape and size of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the poor flow of UHMWPE, several techniques are used to prepare UHMWPE blends, such as melt mixing, coarse powder blending followed by compression molding solvent blending and shear controlled orientation injection molding 4,[10][11] . The incorporation of UHMWPE in other polyethylenes using the solvent blending technique provides good homogeneity, however, is not suitable for large-scale production, since it requires large quantities of solvent and the protocols of mixing affect the final morphology of the blend.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous food packaging, automotive parts, electronic products and construction elements are made from these materials and their blends because of their low density and great damping properties. In the latter case, the application of plastics and polymer blends could also depend on greater resistance to burning [5] and dimensional stability, which is strongly influenced by the thermal shrinkage of the materials [6,7]. During the injection moulding process the shrinkage cannot be ignored because of the density difference between the melted state and the solidified plastic product.…”
Section: Introductionmentioning
confidence: 99%
“…They also found a correlation between the thickness of the forming shell structure and the flowability. Wu et al [7] mentioned that it is necessary to improve the low melting point and decrease the thermal shrinkage of HDPE separator in lithium-ion battery safety, driven by blending or using fillers to avoid the further thickness increasing of the wall. Kang [9] reported that the injection time is the most significant parameter on the volumetric shrinkage of injection moulded products.…”
Section: Introductionmentioning
confidence: 99%